Aqueous leaf extract of Clinacanthus nutans improved metabolic indices and sorbitol‐related complications in type II diabetic rats (T2D) - Umar Imam, Mustapha; Ismail, Maznah; George, Annie; Chinnappan, Sasikala M.; Yusof, Ashril (Wiley Open Access, 2019)
Clinacanthus nutans (Burm. f.) Lindau (C. nutans) has been reported to lower blood glucose level; however, evidence on its efficacy in lowering diabetic complications is limited. The antidiabetic properties of C. nutans aqueous leaf extract on serum metabolic indices, sorbitol production, and aldose reductase enzyme activities in the kidneys, lens, and sciatic nerve of type II diabetic (T2D) rats were evaluated. All rats except normal control rats were fed with a high-fat diet for 8 weeks to induce obesity and subsequently injected with 35 mg/kg streptozotocin to induce type II diabetes. Aqueous leaf extract of C. nutans (100 and 200 mg kg −1 day −1 ) and quercetin (10 mg kg −1 day −1 ) were fed orally for 4 weeks. Diabetic rats administered with C. nutans at 100, 200 mg kg −1 day −1 and quercetin had significantly (p < 0.05) lower fasting blood glucose levels post-intervention: 14.2, 14.0, and 19.9 mm, respectively, compared with the untreated group (22.1 mm). Total cholesterol was significantly (p < 0.05) lower in the C. nutans groups in comparison with the diabetic control group. Levels of F2-isoprostane, a marker of oxidative stress, were attenuated in the presence of the extract. Aldose reductase enzyme activity increased by 64, 99, and 0% and total antioxidant activities by 22, 29, and 126%, respectively. Sorbitol levels in the kidney, lens, and nerve were reduced in diabetic rats administered with C. nutans and quercetin group (by 8, 16, and 3%, respectively). The protective effect of the extract to the liver and kidney was confirmed through liver and kidney enzyme markers and histological analyses. The C. nutans has the potential to attenuate T2D-induced metabolic perturbations and complications related to sorbitol accumulation. © 2019 The Authors. Food Science & Nutrition published by Wiley Periodicals, Inc.